1989
DOI: 10.1007/bf02556022
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aging on fracture healing in the rat

Abstract: The effect of age on the biomechanical properties of healing tibial fractures was studied by comparing the fracture healing in 2-year-old male Wistar rats with the fracture healing in 3-month-old male Wistar rats after 40 and 80 days of healing. There were no significant differences in the mechanical parameters after 40 days of healing, but after 80 days, a considerable delay in the fracture healing process was noted in the old rats compared with the young adult rats when evaluated by maximum load, maximum str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(42 citation statements)
references
References 17 publications
2
39
0
1
Order By: Relevance
“…Conventional orthopaedic wisdom is that ''fractures in children heal faster than those in adults,'' and basic science studies in animals and clinical studies in humans appear to support this clinical experience 21,22 . However, basic science studies of partial transection of the anterior cruciate ligament and patellar tendon healing have suggested that the scar formed in skeletally mature animals is actually stronger than that formed in skeletally immature animals 8,23 .…”
Section: Histologic Resultsmentioning
confidence: 99%
“…Conventional orthopaedic wisdom is that ''fractures in children heal faster than those in adults,'' and basic science studies in animals and clinical studies in humans appear to support this clinical experience 21,22 . However, basic science studies of partial transection of the anterior cruciate ligament and patellar tendon healing have suggested that the scar formed in skeletally mature animals is actually stronger than that formed in skeletally immature animals 8,23 .…”
Section: Histologic Resultsmentioning
confidence: 99%
“…Specifically, patient age was the most important factor in determining new bone density in a recent clinical study [XI. Experimentally, age-related skeletal deficits in intact rats as well as in those healing fractures have also been reported [4,11].…”
Section: Introductionmentioning
confidence: 99%
“…Displacement is more common, and efficacies of some fracture repair techniques decrease relative to younger healthy patients. [3][4][5] Displaced distal radius fractures typically are repaired by closed reduction and casting or open reduction with internal plate fixation, although this treatment dichotomy can be inadequate for certain elderly patients. Re-displacement rates after closed reduction with splinting 6 approach 50%.…”
mentioning
confidence: 99%